Occlusal features of 12 years old Malaysian Malay school-children in Shah Alam/ Majda T. M. Elfseyie, Nagham Mohammed Abdullah and Mohamed Ibrahim Abu Hassan - Elfseyie, Majda T. M.; Mohammed Abdullah, Nagham; Abu Hassan, Mohamed Ibrahim (Faculty of Dentistry, 2014)
To assess the occlusal features, tongue habits, lip competence and their gender dimorphism in 12 years old Malaysian Malay school-children. The method involved clinical examination of 208 subjects from public schools in Shah Alam, Selangor, Malaysia. Occlusal status was assessed according to Angle classification. The following features were also assessed and recorded: overjet, overbite, traumatic overbite, crowding, spacing, midline diastema, cross bite, scissors bite, dental midline shifts, canine displacement, missing teeth, traumatically fractured teeth, tongue thrust and lip competence. Descriptive statistics were used for all measurements; Chi-square was used to assess gender differences. Class I malocclusion is most prevalent in boys and girls (44.0% and 43.8% respectively), followed by Class III malocclusion (31% in boys and 30.4% in girls). Anterior crowding was found in 69.7% of the sample while anterior spacing was found in 30.8%. Incompetent lips were more common in boys than girls. The prevalence of malocclusion in this age group may warrant the need for more preventive and interceptive measures in dental and oral health planning.